Analisis Identifikasi Keberhasilan Implementasi Sistem Keuangan Desa (Siskeudes) Untuk Mewujudkan Akuntabilitas Pada Desa Pematang Serai Kabupaten Langkat - Anggi Pratama Nst; Ikhah Malikhah; Denta Oktari (Jurnal Riset AKuntansi dan Bisnis, 2023)
The Research Approach built with the Qualitative Descriptive method. This study uses primary data sources, namely the Village Head, Village Secretary, Village Treasurer and additions from several community leaders in the Village environment. Then the data obtained and analyzed using descriptive research in obtaining the Strengths, Weaknesses, Opportunities and Threats of each Indicator so as to produce a Strategy for Successful Implementation of the Village Financial System (SISKEUDES). The results of the study identified that the SISKEUDES success strategy in Pematang Serai Village included among others 1) Improving the Quality of Village Vision, Mission and Goals that prioritize national/regional development issues in accordance with the availability of available resources 2) Improving the Quality of the Village Work Program in the RJPMD and RKP which have been analyzed by looking at the potential for income growth and the potential for village spending efficiency 3) Improving the quality of human resources in producing SISKEUDES information through continuous assistance from BPKP 4) Increasing the Development of Quality Human Resources through Cooperation Programs with educational institutions.